Pengaruh Tadarrus Alquran Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Alquran Hadits Di Madrasah Ibtidaiyah Ar-Roja Karangpawitan Garut - Salamudin, Ceceng; Nurdiani, Fitri (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This research is based on the observed low motivation of students in learning the Alquran Hadits subject at Madrasah Ibtidaiyyah (MI) Ar-Roja Karangpawitan, Garut. This lack of motivation is evidenced by students' reluctance to ask questions and express their opinions during lessons. The practice of Tadarrus Alquran offers a potential solution by fostering a closer connection to the Quran through activities such as reading and listening to its recitations. This closer relationship with the Quran can enhance students' motivation to study it, including in the Alquran Hadits subject. The purpose of this study is to describe the impact of Tadarrus Alquran on students' motivation to learn the Alquran Hadits subject at MI Ar-Roja Karangpawitan Garut. The research employs a descriptive quantitative method. Data collection techniques include observation, interviews, document studies, and questionnaires distributed to 25 respondents. Data processing was conducted through statistical analysis. The results indicate that the motivation of students in the Alquran Hadits subject has an average score of 3.976, which falls within the interval of 3.00 - 4.00, categorizing it as "good." This suggests an increase in students' motivation after implementing Tadarrus Alquran in the Alquran Hadits lessons. Meanwhile, the practice of Tadarrus Alquran itself has an average score of 4.056, placing it within the interval of 4.01 – 5.00, which is considered "very good." This indicates that Tadarrus Alquran is an effective solution to enhance students' motivation in learning. Statistical analysis shows that Tadarrus Alquran influences 38.59% of the students' motivation in the Alquran Hadits subject, while 61.41% of the motivation is affected by other variables not examined in this study. Keywords: Tadarrus Alquran, Student Learning Motivation, Alquran Hadits Subject